The Impact of Two Different Cultures on Juvenile Attitudes Toward the Police in China - Wang, Xinting (International journal of offender therapy and comparative criminology, 2020)
This study examines juvenile attitudes toward the police (JATP) from an unconventional angle by examining the possible effect of two different cultures along with more conventional factors typically associated with youth attitude formation. A unique feature of this study is the inclusion of measures of attachment to both the traditional Chinese culture and Western popular culture. The data were collected from 30 minority middle schools with more than 6,500 students in a southern autonomous region in China in 2014. The primary findings indicate that juveniles who are more firmly attached to the traditional Chinese culture and who show respect for parents/teachers tend to hold a more positive view of the police. In contrast, juveniles who endorse Western popular culture and are perceived as a fan of that culture are more likely to hold a negative view of the police, societal actors who are viewed as primary representatives of the mainstream culture.